The Impact of Strategic Leadership style on Institutional Capabilities The Egyptian Travel Agencies as A Case Study - Alramidi, Bassam Samir; Talhi, Fatima Zahra (Finance and Business Economies Review, 2019)
This study aims to identify the impact of strategic leadership on the institutional capabilities by examining its impact on creative behavior, administrative policies, strategic flexibility, organizational effectiveness, employee performance, and knowledge management. The Egyptian travel agencies were selected as case studies. The researchers designed a questionnaire and distributed it to a random sample of the managers of these agencies. 323 questionnaires were analyzed. The study found that strategic leadership affects 69.2% on strategic flexibility, 43.4% on employee performance, 36.2% on creative behavior, 33.2% on knowledge management, 26.5% on administrative policies, and 23.2% on organizational effectiveness.